INCREASING RICE PRODUCTIVITY IN DEGRADED PEATLANDS USING IMPROVED PLANTING METHODS AND RICE VARIETIES - Muhardianto Cahya; Rujito Agus Suwignyo; Erizal Sodikin; Himlal Baral (BIOVALENTIA: Biological Research Journal, 2022)
Sonor farming practical has become a habit for local community of South Sumatra. In fact, this agricultural practice still results in low production. This research was conducted to determine the comparison of planting methods by farmers with improving planting methods with 2 new high yielding varieties. This research was conducted in Perigi Village, Pangkalan Lampam District, Ogan Komering Ilir Regency, South Sumatra Province from December 2019 to April 2020. The research method used was a Split Plot Design with two factors, namely factor 1 was rice varieties and factor 2 was planting method, where the main plot was planting method including: T1: Broadcasting 25 kg/ha, T2: Broadcasting 75 kg/ha, T3: Legowo 2: 1 (20x40x10 cm), and T4: transplanting (20x20 cm) and the sub plot rice varieties, V1: Inpari 30 and V2: Inpara 3. There are 8 treatment combinations with 3 replications. The results showed that the improvement of planting methods showed an increasing in yield in terms of total tiller number, productive tiller number, grain number per panicles, grain weight panicles, grain weight per m2, and plant biomass. The Legowo method had higher productivity than otherplanting method with rice productivity 3.7 tonnes per ha. The Inpara 3 showed better growth and production on degraded peatlands.